Contributing factors affecting job performance at private hospitals in southern region of Malaysia / Munirah Mohd Jidi ...[et al.] - Mohd Jidi, Munirah; Idrus, Syukurriah; Zakirai@Zakaria, Norlida; Eshak, Erratul Shela; Jamian, Nur Faithzah (UiTM Cawangan Johor, 2019)
This research explained the factors that affecting job performance in the Private Hospitals in Southern Region of Malaysia. The objectives of the research were (1) to identify the relationship between of pay and job performance, (2) to determine the relationship between supervision and job performance, (3) to examine the relationship between coworker and job performance. The research was conducted based on three hypothesis which were (1) there was relationship between pay and job performance, (2) there was relationship between co-worker and job performance, (3) there was significant relationship between supervision and job performance. The research design chosen for this study was descriptive and inferential in nature. For this research, the selection of sample was based on the convenience sampling technique. The analysis shows that there is a positive and significant relationship between pay, colleagues, supervision and job performance.